2019
DOI: 10.1108/jmlc-10-2018-0063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cryptocurrency laundering as a complex socio-technical system

Abstract: Purpose The purpose of this paper is to present the findings from a literature review, which aimed to identify previous studies evaluating cryptolaundering from a systems thinking perspective. The aim of this paper is to first confirm that cryptolaundering systems can indeed be defined as complex socio-technical systems and second to present the findings from a systematic review of the literature to determine the extent to which previous research has adopted a systems thinking perspective. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
(65 reference statements)
0
21
0
1
Order By: Relevance
“…Moreover, cryptocurrencies offer discreet and secure avenues for online payment within the scope of dark web marketplace and online black-market transactions (Desmond et al, 2019). The steady growth of e-commerce required a payment method that is equally as trustworthy, anonymous and portable as cash while at the same time allowing international transfers (Drainville, 2012;Merlonghi, 2010).…”
Section: Literature Review 21 Cryptocurrencymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cryptocurrencies offer discreet and secure avenues for online payment within the scope of dark web marketplace and online black-market transactions (Desmond et al, 2019). The steady growth of e-commerce required a payment method that is equally as trustworthy, anonymous and portable as cash while at the same time allowing international transfers (Drainville, 2012;Merlonghi, 2010).…”
Section: Literature Review 21 Cryptocurrencymentioning
confidence: 99%
“…According to Goldman et al (2017), cryptocurrencies can be used to both conceal traditional criminal proceeds and foster an increase in money laundering platforms. Researchers find that cryptocurrencies have been fully integrated into the conventional money-laundering procedure (Ajello, 2014;Desmond et al, 2019;van Wegberg et al, 2018). Bitcoin continues to be the most commonly used cryptocurrency for both legal and illicit transactions (Davidian, 2017;Reynolds and Irwin, 2017).…”
Section: Literature Review 21 Cryptocurrencymentioning
confidence: 99%
“…They presented 51 defense mechanisms to secure the Ethereum ecosystem. In our SLR, we have surveyed articles discussing different cryptocurrencies and did not limit our analysis to a specific cryptocurrency, Other researchers have studied and analyzed a single attack or illegal activity, such as money laundering [84], [85] or cryptojacking [86]. A systematic literature review of the research articles discussing using cryptocurrencies in money laundering (cryptolaundering) from 2009 to 2018 was conducted in [84].…”
Section: Related Workmentioning
confidence: 99%
“…In our SLR, we have surveyed articles discussing different cryptocurrencies and did not limit our analysis to a specific cryptocurrency, Other researchers have studied and analyzed a single attack or illegal activity, such as money laundering [84], [85] or cryptojacking [86]. A systematic literature review of the research articles discussing using cryptocurrencies in money laundering (cryptolaundering) from 2009 to 2018 was conducted in [84]. The study confirmed that cryptolaundering could be considered a complex socio-technical system where multiple entities interact throughout the process, including humans, technical factors, as well as organizational and social factors.…”
Section: Related Workmentioning
confidence: 99%
“…Scientists emphasize that cybersecurity shall be developed in two levels: 1) locally 2) global cooperation of cybersecurity development. Desmond et al (2019) findings are that "the cryptolaundering process is considered to be a complex socio-technical system". Novikovas et al (2017), states, that "countries must feel concern regarding consolidation of their security".…”
Section: Indirect Formsmentioning
confidence: 99%